Effect of Twice-Daily Blue Light Treatment on Matrix-Rich Biofilm Development - Sousa, Denise Lins de; Lima, Ramille Araujo; Zanin, Iriana Carla; Klein, Marlise I. [UNESP]; Janal, Malvin N.; Duarte, Simone (Public Library Science, 2015)
Background The use of blue light has been proposed as a direct means of affecting local bacterial infections, however the use of blue light without a photosensitizer to prevent the biofilm development has not yet been explored. The aim of this study was to determine how the twice-daily treatment with blue light affects the development and composition of a matrix-rich biofilm. Methodology/Principal Findings Biofilms of Streptococcus mutans UA159 were formed on saliva-coated hydroxyapatite discs for 5 days. The biofilms were exposed twice-daily to non-coherent blue light (Luma-Care; 420 nm) without a photosensitizer. The distance between the light and the sample was 1.0 cm; energy density of 72 J cm(-2); and exposure time of 12 min 56 s. Positive and negative controls were twice-daily 0.12% chlorhexidine (CHX) and 0.89% NaCl, respectively. Biofilms were analyzed for bacterial viability, dry-weight, and extra (EPS-insoluble and soluble) and intracellular (IPS) polysaccharides. Variable pressure scanning electron microscopy and confocal scanning laser microscopy were used to check biofilm morphology and bacterial viability, respectively. When biofilms were exposed to twice-daily blue light, EPS-insoluble was reduced significantly more than in either control group (CHX and 0.89% NaCl). Bacterial viability and dry weight were also reduced relative to the negative control (0.89% NaCl) when the biofilms were treated with twice-daily blue light. Different morphology was also visible when the biofilms were treated with blue light. Conclusions Twice-daily treatment with blue light without a photosensitizer is a promising mechanism for the inhibition of matrix-rich biofilm development.